Hrm Practices, Workplace Bullying And Turnover Intention: The Roles Of Work Engagement And Perceived Support - Paul, Gadi Dung (2020)
The public universities in Nigeria face a high turnover rate among its academicians. The main objective of this study is to examine the relationship between HRM practices, workplace bullying, and turnover intention of academicians in the top 10 public universities in Nigeria. The study also investigated the mediating role of work engagement on the relationship between HRM practices and workplace bully on turnover intention and the moderating role of perceived organizational support and perceived supervisor support on the relationship between work engagement and turnover intention. There was a need to conduct the study because of inconsistency or weak relationship between HRM practices, workplace bullying, and work engagement with turnover intention of academicians in the public universities in Nigeria.